Determination of malic acid in real samples by using enzyme immobilized reactors and amperometric detection - Manzoli, A.; Tomita, LSN; Fertonani, F. L.; de Oliveira-Neto, G.; Mascini, M.; Yamanaka, H. (Taylor & Francis Inc, 2004)
The malate dehydrogenase (MDH) and ascorbate oxidase were immobilized independently, onto silanized controlled porous silica and packed in a tygon tube. The reactors were inserted in the flow system, and the malic acid was determined by measurement of NADH produced by enzymatic reaction. The NADH was reoxidized in a wall jet cell that consisted of spectrographic graphite, Ag/AgCl, KCl(sat), and steel needle as work, reference, and counter electrodes, respectively. The current intensities were measured at 390 mV. The malate calibration curve shows a linear range from 5.0 x 10(-6) to 1.0 x 10(-4) molL(-1), the lifetime was 40 analyses, after that a decrease of 20% on the response is observed. Three different citric juices were analyzed and a good correlation between the proposed method and spectrophotometric commercial kit were obtained.
Keywords: citrus juice; malic acid; malate dehydrogenase; ascorbic acid